The antecedents and effects of app evolution: a co-evolutionary perspective. (13th April 2022) - Tian, Hengqi; Lin, Feiyan; Guo, Bingchen; Zhao, Jing
B2C platforms have increasingly relied on applications (apps) to conduct business and compete fiercely with rivals and complementors in the contest of app evolution. The extant digital innovation and digital platform literature mainly study antecedents of app evolution from the platform perspective and with scant attention on how intra-platform competition affects app evolution. Based on Red Queen competition theory and the platform envelopment literature, we investigate how the coevolutionary competition with rival and complementor apps affects the evolution of the focal app and the subsequent effects on its market performance. Our empirical results unveil an inverted U-shaped relationship between app evolution and market performance and show that rival app evolution decreases the rate at which the B2C app evolves, while complementor app evolution escalates the evolution rate. Theoretical and practical implications are discussed.